Comparison of Athletics Records of Intellectually Disabled Persons with Records of Intact Athletes - Pavel Tilinger (Karolinum Press, 2014)
Comparison of Athletics Records of Intellectually Disabled Persons with Records of Intact Athletes Comparative studies between intact and ID (Intellectually Disabled) individuals have been carried out in many areas (psychic, somatic characteristics, motor skills of individuals with ID, comparison of the level of intellect and motor performance). The study compares the records of intellectually disabled athletes with the records of majority population athletes. For comparison, we have used the existing world records registered by the International Association of Athletics Federations (IAAF), and Inas, (International Sports Federation for Persons with Intellectual Disability). To compare the best Czech records with world records, the best performances of women registered by the ČSMPS (Czech Sports Association for the Mentally Handicapped) were used. If we compare the World Records (IAAF and Inas), we can find differences ranging from 8.2 to 45.3%. The differences between intact and intellectually disabled men are approx. by 2 to 10% lower than in women's similar events. It is only in three events that the differences between intact and ID are slightly lower in women than in men (high jump, discus throw, javelin throw). The smallest differences between the IAAF and Inas records are in sprints events and middle running distances of men and women (10% men, or 15% women respectively). The differences in long distances reach 18% (men) and 23% (women). The differences in jumping events are very different, accounting for 20% for men and 24% for women with some generalization. Throwing events for practically both sexes bring differences above 40% (except for shot put). Srovnání atletických rekordů intelektově postižených osob s rekordy intaktních sportovců Srovnávací studie mezi IP a intaktními byly realizovány v řadě oblastí (psychika, somatické charakteristiky, motorika jedinců s IP, srovnání úrovně intelektu a motorické výkonnosti). Studie přináší srovnání rekordních výkonů intelektuálně postižených atletů s rekordy sportovců většinové populace. Pro komparaci jsme využili stávající světové rekordy vedené mezinárodní atletickou federací IAAF a Inas, (mezinárodní organizací pro paralelní sport pro osoby s intelektovým postižením). Pro srovnání českých nejlepších atletek se světem byly využity rekordy ČSMPS (Českého svazu mentálně postižených sportovců, žen). Ze srovnání světových rekordů (IAAF a Inas) vyplývají diference na úrovni 8,2-45,3 %. Diference mezi intaktními a intelektově postiženými muži jsou o cca 2-10 % nižší než u obdobných disciplín žen. Pouze u tří disciplín jsou rozdíly mezi intaktními a IP u žen nepatrně nižší nežli u mužů (skok vysoký, hod diskem, hod oštěpem). Nejmenší rozdíl mezi rekordy IAAF a Inas je u sprintů a středních tratí mužů i žen (10 % u mužů, resp. 15 % u žen) Rozdíly na dlouhých tratích dosahují 18 % (u mužů) a 23 % (u žen). Ve skokanských disciplínách jsou diference velmi různé, při určitém zobecnění 20 % u mužů a 24 % u žen. Vrhačské disciplíny prakticky u obou pohlaví přináší rozdíly nad 40 % (vyjma vrhu koulí).